2022
DOI: 10.1088/1361-6560/ac692e
|View full text |Cite
|
Sign up to set email alerts
|

Millisecond speed deep learning based proton dose calculation with Monte Carlo accuracy

Abstract: Objective: Next generation online and real-time adaptive radiotherapy workflows require precise particle transport simulations in sub-second times, which is unfeasible with current analytical pencil beam algorithms (PBA) or Monte Carlo (MC) methods. We present a deep learning based millisecond speed dose calculation algorithm (DoTA) accurately predicting the dose deposited by mono-energetic proton pencil beams for arbitrary energies and patient geometries. Approach: Given the forward-scattering nature of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…It was recently shown that the transformer architecture is very suitable for dose deposition predictions in the case of the proton beam therapy 17,19 . Transformer models rely on the prediction of sequences to sequences utilizing the so‐called attention mechanism 18 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recently shown that the transformer architecture is very suitable for dose deposition predictions in the case of the proton beam therapy 17,19 . Transformer models rely on the prediction of sequences to sequences utilizing the so‐called attention mechanism 18 .…”
Section: Methodsmentioning
confidence: 99%
“…17,19 Transformer models rely on the prediction of sequences to sequences utilizing the so-called attention mechanism. 18 In the case of the model of interest, named DoTA, 17,19 the source sequence comprises density matrix tokens, which were obtained from encoding the phantom tissue density matrix slice by slice using a convolutional encoder. The target sequence comprises energy deposition tokens which are decoded via a convolutional decoder into energy deposition slices.…”
Section: Transformer-based Modelmentioning
confidence: 99%
See 3 more Smart Citations